Better Data, Better Results : Remote Sensing as a Tool for Monitoring Water Quality in Lake Toba, Indonesia - World Bank (World Bank, Washington, DC, 2019)
Lake Toba is a unique natural asset of global significance with a rich cultural heritage located in the North Sumatra Province of Indonesia. Located 904 meters above sea level and with a maximum depth of more than 500 meters, this 87-kilometer-long lake provides a wide range of economic and environmental goods and services for more than half a million people and 400 villages in the seven districts covered by the lake's 3,658 square kilometer catchment. However, sustaining the long-term economic and environmental value of Lake Toba depends on addressing the deterioration of water quality. This technical guidance note reports on the potential benefits of using remote sensing as part of an integrated strategy to improve the monitoring and management of water quality in Lake Toba.